Islamic Pawnbroking in Scholarly Discourse: Trends, Gaps, and Future Directions - Ma'ruf, Aminudin; Hasanah, Silvya Miftahul; Hakim, Lukmanul; Umam, Fachru Nurul (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
The development of Islamic pawnbroking (Ar-Rahnu) as a short-term financing mechanism presents a promising solution for poverty alleviation by supporting small and medium-sized entrepreneurs. This study aims to visualize the progress and research trends in Islamic pawnbroking using bibliometric analysis. Data were collected from the Scopus database, where an initial search conducted on September 16, 2022, retrieved 168 documents, later refined to 101 articles based on inclusion criteria. The dataset was analyzed using VOSviewer to generate visualizations of keyword co-occurrence, author collaboration, citation patterns, and thematic clusters. Findings show a steady increase in scholarly output from 1913 to 2022, with significant growth post-2010. However, the field faces persistent challenges such as low public awareness, preference for conventional pawnshops, and unregulated financial practices. The study suggests strategic improvements for Islamic pawnbroking, including product diversification, targeted marketing, and public re-education to broaden its appeal beyond low-income users. The bibliometric mapping also identifies potential research directions, particularly in microenterprise financing and socio-economic empowerment through Islamic financial services.======================================================================================================== ABSTRAK - Pegadaian Syariah dalam Wacana Akademik: Tren, Kesenjangan, dan Arah Penelitian ke Depan. Perkembangan pegadaian syariah (Ar-Rahnu) sebagai mekanisme pembiayaan jangka pendek merupakan solusi yang menjanjikan untuk mengatasi kemiskinan melalui dukungan kepada pengusaha kecil dan menengah. Penelitian ini bertujuan untuk memvisualisasikan kemajuan dan tren penelitian dalam bidang pegadaian syariah dengan menggunakan analisis bibliometrik. Data dikumpulkan dari basis data Scopus, di mana pencarian awal pada tanggal 16 September 2022 menemukan 168 dokumen, yang kemudian disaring menjadi 101 artikel berdasarkan kriteria inklusi. Dataset dianalisis menggunakan VOSviewer untuk menghasilkan visualisasi keterkaitan kata kunci, kolaborasi penulis, pola kutipan, dan klaster tematik. Temuan menunjukkan peningkatan stabil dalam publikasi ilmiah dari tahun 1913 hingga 2022, dengan lonjakan signifikan pasca-2010. Namun, bidang ini masih menghadapi tantangan seperti rendahnya kesadaran masyarakat, preferensi terhadap pegadaian konvensional, dan praktik keuangan yang tidak teregulasi. Studi ini menyarankan peningkatan strategis dalam pegadaian syariah, termasuk diversifikasi produk, pemasaran yang ditargetkan, dan edukasi publik untuk memperluas daya tariknya di luar kelompok berpenghasilan rendah. Pemetaan bibliometrik juga mengidentifikasi arah penelitian potensial, khususnya dalam pembiayaan usaha mikro dan pemberdayaan sosial ekonomi melalui layanan keuangan Islam.